Composite separator and battery

CN224862417UActive Publication Date: 2026-10-16SHENZHEN SENIOR TECH MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202522204935.8
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2026-10-16
Estimated Expiration
2035-10-17

AI Technical Summary

Technical Problem

[0003]为满足日益提升的安全性要求,单一的聚烯烃隔膜(如PE、PP)已难以胜任

Benefits of technology

[0016] This invention provides a composite separator and a battery. In the composite separator system described above, the first adhesive layer 300 helps improve the interfacial adhesion and adhesion strength between the composite separator and the electrode (or electrode sheet). Both the first adhesive layer 300 and the first base film 100 have through-hole 101 structures, and the through-holes 101 of the two are corresponding to and interconnected, which helps improve the ion transport rate of the composite separator and improve the rate performance of the battery. The second base film 200 has a porous three-dimensional network structure, which can not only form a good liquid storage space but also provide channels for ion transport and provide mechanical support for the composite separator. At the same time, the second adhesive layer 302 is arranged in an island structure between the first base film 100 and the second base film 200, ensuring the ion transport channels while tightly connecting the first base film 100 and the second base film 200, improving the integrity between the film layers. Thus, the first base film 100, the second base film 200, and the adhesive layer synergistically improve the mechanical strength and ion conductivity of the composite separator. Therefore, the composite membrane of this invention has excellent ion transport rate, mechanical strength and interfacial adhesion to the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224862417U_ABST
    Figure CN224862417U_ABST
Patent Text Reader

Abstract

The utility model provides a kind of composite diaphragm and battery, including first adhesive layer, first base film, second adhesive layer and second base film that are sequentially laminated;The first base film has straight-through hole structure, the second base film has porous three-dimensional network structure, and second adhesive layer is island structure;The first adhesive layer has straight-through hole structure, and the straight-through hole of the first adhesive layer and the straight-through hole of the first base film correspond to each other and are through. The utility model is helpful to improve the ion transmission rate of composite diaphragm, mechanical strength and interface adhesion with electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to the field of diaphragm technology, specifically to a composite diaphragm and a battery. Background Technology

[0002] As a crucial component of lithium-ion batteries, the separator is located between the positive and negative electrodes. Its core function is to prevent short circuits between the two electrodes while allowing ions in the electrolyte to pass freely through, completing the charging and discharging process. Therefore, the performance of the separator, especially its ionic conductivity, mechanical strength, and interfacial adhesion between the separator and the electrodes, directly determines the overall performance and safety of the battery.

[0003] To meet increasingly stringent safety requirements, single polyolefin membranes (such as PE and PP) are no longer sufficient. Therefore, composite membranes have emerged, typically employing a strategy of layering materials with different properties to combine the advantages of each material. Utility Model Content

[0004] This invention provides a composite separator and a battery, which helps to improve the ion transport rate, mechanical strength and interfacial adhesion of the composite separator to the electrode.

[0005] This invention provides a composite membrane, comprising a first adhesive layer, a first base membrane, a second adhesive layer, and a second base membrane stacked sequentially; the first base membrane has a through-hole structure, the second base membrane has a porous three-dimensional network structure, and the second adhesive layer has an island structure; the first adhesive layer has a through-hole structure, and the through-holes of the first adhesive layer correspond to and are interconnected with the through-holes of the first base membrane.

[0006] Optionally, the thickness of the second adhesive layer is 0.1 μm to 1 μm.

[0007] Optionally, the composite membrane further includes an adhesive polymer disposed on the sidewall of the through-hole of the first base membrane and close to the second base membrane; preferably, the stacking height of the adhesive polymer is 0.1 μm to 2 μm; preferably, the adhesive polymer is selected from polyimide, polyetherimide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, polyvinyl alcohol, epoxy resin, polyurethane or polyvinyl acetate.

[0008] Optionally, the pore density of the through-holes in the first base film is 2×10⁻⁶. 9 pcs / m 2 ~2×10 10 pcs / m 2 ; and / or, the average pore size of the through-holes in the first base film is 1 μm to 10 μm; and / or, the thickness of the first base film is 5 μm to 10 μm.

[0009] Optionally, the first base film is selected from one or more of polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalenedicarboxylate.

[0010] Optionally, the thickness of the second base film is 3 μm to 5 μm; and / or, the average pore size of the pores in the second base film is 1 nm to 100 nm; and / or, the porosity of the second base film is 30% to 60%.

[0011] Optionally, the second base film includes a polyolefin substrate, or a polyolefin substrate and a coating disposed on at least one surface of the polyolefin substrate, wherein the coating is selected from inorganic ceramic coatings, organic polymer coatings, or nanofiber coatings.

[0012] Optionally, the polyolefin substrate is selected from at least one or any two of polyethylene film, polypropylene film, and polybutene film to form a composite substrate film.

[0013] Optionally, the thickness of the first adhesive layer is 0.1 μm to 2 μm; and / or, the average pore size of the through holes in the first adhesive layer is 1 μm to 10 μm;

[0014] Optionally, the first adhesive layer and the second adhesive layer are each independently selected from polyimide, polyetherimide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, polyvinyl alcohol, epoxy resin, polyurethane or polyvinyl acetate.

[0015] This invention provides a battery comprising the composite separator described above.

[0016] This invention provides a composite separator and a battery. In the composite separator system described above, the first adhesive layer 300 helps improve the interfacial adhesion and adhesion strength between the composite separator and the electrode (or electrode sheet). Both the first adhesive layer 300 and the first base film 100 have through-hole 101 structures, and the through-holes 101 of the two are corresponding to and interconnected, which helps improve the ion transport rate of the composite separator and improve the rate performance of the battery. The second base film 200 has a porous three-dimensional network structure, which can not only form a good liquid storage space but also provide channels for ion transport and provide mechanical support for the composite separator. At the same time, the second adhesive layer 302 is arranged in an island structure between the first base film 100 and the second base film 200, ensuring the ion transport channels while tightly connecting the first base film 100 and the second base film 200, improving the integrity between the film layers. Thus, the first base film 100, the second base film 200, and the adhesive layer synergistically improve the mechanical strength and ion conductivity of the composite separator. Therefore, the composite membrane of this invention has excellent ion transport rate, mechanical strength and interfacial adhesion to the electrode. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of this utility model or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this utility model. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 A longitudinal cross-sectional schematic diagram of the composite diaphragm provided in an embodiment of this utility model;

[0019] Figure 2 Scanning electron microscope image of the first base film side surface of the composite diaphragm provided in this embodiment of the present invention;

[0020] Figure 3 A scanning electron microscope image of the second base membrane side surface of the composite diaphragm provided in an embodiment of this utility model.

[0021] Explanation of reference numerals in the attached figures:

[0022] 100 - First base film; 200 - Second base film; 300 - First adhesive layer; 101 - Through-hole structure; 301 - Adhesive polymer; 302 - Second adhesive layer. Detailed Implementation

[0023] To enable those skilled in the art to better understand the present invention, a further detailed description of the present invention is provided below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only used to explain the present invention and are not intended to limit its scope. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the protection scope of the present invention.

[0024] As a crucial component of lithium-ion batteries, the separator plays a key role in enhancing their safety performance during use and cycling. Within the entire battery cell system, the separator not only needs excellent electrochemical performance, such as electrochemical stability and lithium-ion conductivity, but also superior non-electrochemical properties, such as adhesion, high thermal stability, high porosity, and uniform pore size distribution. However, existing composite separators still present numerous challenges in practical applications. For instance, the layered composite structure inevitably introduces additional interfaces, increasing ion transport resistance. Furthermore, thermal pressing can easily lead to thermal collapse of the substrate's pore structure, blocking ion channels and resulting in insufficient interlayer bonding and mechanical integrity. Additionally, polyolefin separators lack effective adhesion to the electrode active materials, leading to instability at the electrode-separator interface during charging and discharging, easily causing relative displacement, increasing interfacial impedance, and affecting the battery's long-term cycle stability and safety.

[0025] Therefore, there is an urgent need to develop a lithium battery separator that combines ion transport rate, mechanical strength, and adhesion to electrodes.

[0026] This utility model embodiment provides a composite diaphragm, such as Figure 1 As shown, the structure includes a first adhesive layer 300, a first base film 100, a second adhesive layer 302, and a second base film 200 stacked sequentially. The first base film 100 has a through-hole structure 101, the second base film 200 has a porous three-dimensional network structure, and the second adhesive layer 302 has an island structure. The first adhesive layer 300 has a through-hole structure 101, and the through-holes of the first adhesive layer 300 correspond to and are interconnected with the through-holes of the first base film 100.

[0027] According to research and analysis, the first adhesive layer 300 helps improve the interfacial adhesion and bonding strength between the composite separator and the electrode (or electrode sheet). Both the first adhesive layer 300 and the first base film 100 have through-hole structures 101, and the through-holes of the two are corresponding and interconnected, which helps improve the ion transport rate of the composite separator and improve the rate performance of the battery. The second base film 200 has a porous three-dimensional network structure, which not only forms a good liquid storage space but also provides channels for ion transport and provides mechanical support for the composite separator. At the same time, the second adhesive layer 302 is arranged in an island structure between the first base film 100 and the second base film 200, ensuring the ion transport channels while tightly connecting the first base film 100 and the second base film 200, improving the integrity between the film layers. Thus, the first base film 100, the second base film 200, and the adhesive layer synergistically improve the mechanical strength and ion conductivity of the composite separator. Therefore, the composite separator of this invention has excellent ion transport rate, mechanical strength, and interfacial adhesion with the electrode.

[0028] The second adhesive layer 302 can be an independent island structure or a continuous island structure.

[0029] In some embodiments, the thickness of the second adhesive layer 302 is 0.1 μm to 1 μm, for example, a range of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm or any combination thereof, which helps to promote a tight connection between the first base film 100 and the second base film 200, helps to improve the interlayer contact performance of the composite separator, and is beneficial to further improve the mechanical strength and ionic conductivity of the composite separator.

[0030] The method for testing the thickness of the second adhesive layer is not particularly limited. It can be obtained by referring to GB / T 36363-2018, or by randomly selecting 10 points on the cross-sectional SEM image of the composite diaphragm to measure its thickness and calculating the average thickness of the 10 measurement points as the thickness of the second adhesive layer.

[0031] In some embodiments, the composite separator further includes an adhesive polymer 301 disposed on the sidewall of the through-hole of the first base membrane 100 and close to the second base membrane 200. The adhesive polymer 301 can promote a tight connection between the first base membrane 100 and the second base membrane 200, thereby helping to improve the interlayer contact performance of the composite separator, and also helping to improve the speed of electrolyte wetting of the through-holes and the electrolyte retention effect, which is beneficial to further improving the mechanical strength and ionic conductivity of the composite separator.

[0032] Specifically, the stacking height of the adhesive polymer 301 can be 0.1 μm to 2 μm, for example, a range of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm or any combination thereof.

[0033] The stacking height of the adhesive polymer 301 refers to the maximum vertical distance between the stack of adhesive polymer 301 and the surface of the second base membrane. It can be obtained by testing the following method: randomly select 10 stacking points of the stacked polymer 301 from the SEM image of the composite membrane cross section, measure the vertical height from the highest stacking point to the surface of the second base membrane, and calculate the average stacking height of the 10 measurement points as the stacking height of the adhesive polymer.

[0034] Furthermore, the adhesive polymer can be selected from polyimide, polyetherimide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, polyvinyl alcohol, epoxy resin, polyurethane or polyvinyl acetate.

[0035] To further improve ionic conductivity while ensuring the mechanical strength of the first base film 100, in some embodiments, the pore density of the through-holes in the first base film 100 is 2 × 10⁻⁶. 9 pcs / m 2 ~2×10 10 pcs / m 2 .

[0036] Pore ​​density can be obtained by the following method: The surface of the first base film treated with platinum (Pt) deposition was observed using a scanning electron microscope (SEM) at an accelerating voltage of 2kV, a magnification of 1000x, and a field of view of 100μm × 100μm, and a surface SEM image (secondary electron image) was captured. The captured surface SEM image was binarized using HALCON 13 software from MVTec to extract pores. As an image processing method, the surface SEM image was subjected to a 3-pixel × 3-pixel mean filter to remove noise, followed by a 21-pixel × 21-pixel mean filter. Subsequently, based on the grayscale value of the filtered image, a dynamic threshold of -30 grayscale was set for binarization to extract the dark areas in the image (denoted as "Image Processing 1"). Each independent, continuous dark area extracted was counted as a pore. The total number of pores within the 100μm × 100μm field of view was counted, and then the number of pores per square meter (m²) was calculated through unit conversion. 2 The number of pores within the field of view is the pore density.

[0037] Considering the battery's internal resistance and mechanical strength, in some embodiments, the thickness of the first base film 100 is 5μm to 10μm, for example, a range of 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or any combination thereof.

[0038] The method for testing the thickness of the first base film is not particularly limited. It can be obtained by referring to GB / T 36363-2018, or by randomly selecting 10 points on the cross-sectional SEM image of the composite diaphragm to measure the thickness, and calculating the average thickness of the 10 measurement points as the thickness of the first base film.

[0039] Figure 2 A scanning electron microscope image of the side surface of the first base membrane 100 of the composite diaphragm provided in an embodiment of this utility model. (See image below.) Figure 2 As shown, the first base membrane 100 of the composite diaphragm has through holes distributed on its side surface.

[0040] In some embodiments, the average pore size of the through holes in the first base membrane 100 is 1μm to 10μm, for example, a range of 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or any combination thereof, which is beneficial to improve the mechanical strength of the first base membrane while reducing the internal resistance of the composite diaphragm.

[0041] Furthermore, the first base film 100 may include polymers with melting points higher than 200°C. The high melting temperature of the first base film 100 can be significantly higher than that of the conventional second base film 200. When the battery temperature reaches the melting temperature of the second base film 200, the first base film 100 can still maintain the original structure of the composite separator, thereby increasing the membrane breakage temperature of the composite separator, avoiding thermal shrinkage, and thus preventing battery short circuits and effectively improving battery safety.

[0042] In some embodiments, the first base film 100 may be selected from one or more of polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalenedicarboxylate.

[0043] Figure 3 A scanning electron microscope image of the side surface of the second base membrane 200 of the composite diaphragm provided in an embodiment of this utility model. (See image.) Figure 3 As shown, the second base membrane 200 has a porous three-dimensional network structure.

[0044] Considering the battery's internal resistance and mechanical strength, in some embodiments, the thickness of the second base film 200 is 3μm to 5μm, for example, 3μm, 4μm, 5μm or any combination thereof.

[0045] The method for testing the thickness of the second base film is not particularly limited. It can be obtained by referring to GB / T 36363-2018, or by randomly selecting 10 points on the cross-sectional SEM image of the composite diaphragm to measure the thickness of the second base film and calculating the average thickness of the 10 measurement points as the thickness of the second base film.

[0046] To further improve ionic conductivity while ensuring the mechanical strength of the second base film 200, in some embodiments, the average pore size of the pores in the second base film 200 is 1 nm to 100 nm, for example, a range of 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any combination thereof.

[0047] The average pore size of the first and second base films can be obtained by measuring the pore size using a Perm Porometer (PMI CFP-1500A) in the order of dry-up followed by wet-up.

[0048] The specific calculation method for the average orifice diameter is as follows: Based on the 1 / 2 slope line of the "Wet-up" measurement curve and the "Dry-up" measurement curve (which represents the relationship between pressure and flow rate), the pressure value corresponding to the intersection of the two curves is converted into orifice diameter.

[0049] The conversion between pressure (P) and orifice diameter (d) is performed using the following mathematical formula:

[0050]

[0051] In the formula: d is the aperture in micrometers (μm); γ is the surface tension of the liquid used in the test in millinewtons per meter (mN / m); P is the pressure in Pascals (Pa); and C is the instrument constant.

[0052] To ensure that the second base membrane 200 has good mechanical strength and to further provide sufficient liquid storage space and ion transport path, in some embodiments, the porosity of the second base membrane 200 is 30% to 60%, for example, 30%, 40%, 50%, 60% or any combination thereof.

[0053] The porosity of the second base membrane was obtained by testing in accordance with GB / T 36363-2018.

[0054] Furthermore, the second base film 200 can be a polyolefin film. The melting temperature of this second base film is significantly lower than that of the aforementioned first base film 100. When the battery temperature reaches the melting temperature of the second base film 200, the second base film 200 melts and closes or fills the pores in its three-dimensional network structure, thereby suppressing or preventing short circuits. Although the battery temperature may continue to rise at this time, the first base film 100 will not melt because its melting temperature is higher. This maintains the original structure of the composite separator, increases the membrane breakage temperature of the composite separator, avoids thermal shrinkage, and thus avoids battery short circuits. Therefore, the composite separator including the aforementioned first base film 100 has good heat resistance and a self-closing mechanism, which can effectively improve battery safety.

[0055] Preferably, the second base film 200 may include a polyolefin substrate, or the second base film 200 may include a polyolefin substrate and a coating disposed on at least one surface of the polyolefin substrate, wherein the coating is selected from inorganic ceramic coatings, organic polymer coatings or nanofiber coatings.

[0056] The ceramic particles used in inorganic ceramic coatings can be selected from SiO2, TiO2, Al2O3, boehmite, Y2O3, ZrO2, yttrium-stabilized zirconium oxide (YSZ), LATP, and Li7La3Zr2O. 12 One or more of them.

[0057] The organic polymer in the organic polymer coating can be selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, and polyvinyl alcohol.

[0058] The nanofibers used in the nanofiber coating can be selected from one or more of halloysite nanofibers, cellulose nanofibers, boron carbide nanowires, copper hydroxide nanowires, silicon monoxide nanowires, and hydroxyapatite nanowires.

[0059] The aforementioned polyolefin substrate may be selected from at least one of polyethylene film, polypropylene film, polybutene film (polybutene-1 film), or a composite substrate film formed by stacking any two of them.

[0060] That is, the second base film 200 can be a single-layer film or a composite film of two or more layers.

[0061] For example, the second base film 200 can be a composite film of two or more layers of polyethylene and polypropylene, a composite film of two or more layers of polyethylene and polybutene, or a composite film of two or more layers of polypropylene and polybutene.

[0062] The aforementioned second base film 200 can provide good pore-closing performance, which is beneficial to improving the electrochemical safety performance of the battery.

[0063] Based on the consideration of effectively suppressing excessive penetration of the first adhesive layer into the through-pores of the first base film during the hot-pressing process of battery fabrication, which would affect ion transport and ensure electrode adhesion, and in some embodiments, the thickness of the first adhesive layer is 0.1μm to 2μm, for example, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 2μm or any combination thereof, which also helps to make the composite separator have both high strength and low air permeability.

[0064] The method for testing the thickness of the first adhesive layer is not particularly limited. Ten points of the first adhesive layer can be randomly selected from the SEM image of the composite diaphragm cross section to measure the thickness, and the average thickness of the ten measurement points can be calculated as the thickness of the first adhesive layer.

[0065] In some embodiments, the average pore size of the through holes in the first adhesive layer is 1 μm to 10 μm, for example, a range of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any combination thereof. This helps to ensure that the adhesive layer has sufficient bonding points with the electrode (electrode sheet) to further improve adhesion, while ensuring that the ion transport channels improve ion transport performance. It also helps to enable the composite membrane to have both high strength and low air permeability.

[0066] The average pore size of the first adhesive layer can be obtained using a pore size analyzer (Perm Porometer, PMI CFP-1500A) in a dry-up, wet-up sequence. Alternatively, the pore size can be measured by randomly selecting 10 pores in the first adhesive layer from a cross-sectional SEM image of the composite diaphragm. For each pore size, three measurement points are selected along the thickness direction, and the average value of these 30 measured pore sizes is calculated as the average pore size of the first adhesive layer.

[0067] In some embodiments, the first adhesive layer and the second adhesive layer are each independently selected from polyimide, polyetherimide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, polyvinyl alcohol, epoxy resin, polyurethane or polyvinyl acetate.

[0068] This utility model embodiment also provides a method for preparing the above-mentioned composite separator, comprising: dispersing an adhesive polymer in a solvent to obtain an adhesive polymer coating slurry; stacking a first base film (reinforcing layer) and a second base film (closed-cell layer) together; then coating the adhesive polymer coating slurry onto the surface of the first base film away from the second base film to form a first adhesive layer; then the adhesive polymer coating slurry to be coated on the surface of the first base film away from the second base film permeates through the through-holes of the first base film to the space between the first base film and the second base film to form a second adhesive layer; then removing the solvent to obtain the composite separator.

[0069] In some embodiments, the solvent may include one or more of water, ethanol, acetone, N-methylpyrrolidone, and tetrahydrofuran.

[0070] Specifically, the first base film (reinforcing layer) can be prepared by heavy ion radiation penetration and chemical etching, or by laser drilling, because the first base film can be called a heavy ion microporous film.

[0071] The second base film (closed-pore layer) can be prepared by thermally induced separation or stretching pore formation.

[0072] During the coating process described above, due to the wetting and diffusion of the adhesive polymer coating slurry, the adhesive polymer coating slurry coated on the through-hole portion of the first base film will penetrate through the through-hole of the first base film to the space between the first base film and the second base film, forming a second adhesive layer, thereby achieving a high-strength composite between the first base film and the second base film. Then, the solvent in the adhesive polymer coating slurry is removed to obtain a composite membrane (multilayer composite membrane).

[0073] In some embodiments, the coated side of the surface of the second base film may be corona treated to allow the adhesive polymer coating slurry to better wet and diffuse into the pores of the second base film.

[0074] In some embodiments, the process of removing solvent from the adhesive polymer coating slurry can be achieved by drying methods such as roller contact heating drying or hot air drying.

[0075] There are no particular limitations on drying temperature and drying time, as long as the solvent in the adhesive polymer coating slurry is completely removed and the integrity of the composite membrane is maintained.

[0076] In some embodiments, the drying temperature can be below 70°C, and the drying time can be between 30 and 60 seconds.

[0077] This utility model embodiment also provides a battery, including the above-described composite separator.

[0078] The present invention will be further described below through specific embodiments and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, materials and instruments, all of which are commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.

[0079] Composite membranes of Examples 1-4

[0080] The composite membrane of each embodiment includes a first adhesive layer, a first base membrane, a second adhesive layer, and a second base membrane stacked sequentially; the first base membrane has a through-hole structure, the second base membrane has a porous three-dimensional network structure, and the second adhesive layer has an island structure; the first adhesive layer has a through-hole structure, and the through-holes of the first adhesive layer correspond to and communicate with the through-holes of the first base membrane; it also includes an adhesive polymer, which is disposed on the sidewall of the through-hole of the first base membrane and close to the side of the second base membrane.

[0081] The material, thickness, pore structure, average pore size, and pore density of the first base membrane, the material, thickness, pore structure, average pore size, and pore density of the second base membrane, the material, thickness, pore structure, and average pore size of the first adhesive layer, the material and thickness of the second adhesive layer, and the material and stacking height of the bonding polymer are shown in Tables 1 and 2.

[0082] Comparative Example 1

[0083] The difference between the composite membrane of this comparative example and the composite membrane of Example 1 is that it does not include the first adhesive layer and the adhesive polymer. Other differences are shown in Tables 1 and 2.

[0084] The material, thickness, pore structure, average pore size, and pore density of the first base membrane of the composite membrane in Comparative Example 1, the material, thickness, pore structure, average pore size, and pore density of the second base membrane, and the thickness of the second adhesive layer are shown in Tables 1 and 2.

[0085] Comparative Example 2

[0086] The difference between the composite membrane in this comparative example and the composite membrane in Example 1 is that the first base membrane has a three-dimensional network structure. Other differences are shown in Tables 1 and 2.

[0087] The materials, thickness, pore structure, average pore size, and pore density of the first base membrane, the materials, thickness, pore structure, average pore size, and pore density of the second base membrane, the materials, thickness, pore structure, and average pore size of the first adhesive layer, the materials and thickness of the second adhesive layer, and the materials and stacking height of the bonding polymers of Comparative Example 2 are shown in Tables 1 and 2.

[0088] Comparative Example 3

[0089] The difference between the composite membrane in this comparative example and the composite membrane in Example 1 is that the second base membrane has a through-hole structure. Other differences are shown in Tables 1 and 2.

[0090] The materials, thickness, pore structure, average pore size, and pore density of the first base membrane, the materials, thickness, pore structure, average pore size, and pore density of the second base membrane, the materials, thickness, pore structure, and average pore size of the first adhesive layer, the materials and thickness of the second adhesive layer, and the materials and stacking height of the bonding polymers of Comparative Example 3 are shown in Tables 1 and 2.

[0091] Table 1

[0092]

[0093] Table 2

[0094]

[0095] Test case

[0096] The following parameters of the composite membranes of each embodiment and comparative example were tested:

[0097] Mechanical strength: Tested in accordance with standard GB-T 36363-2018 "Polyolefin separator for lithium-ion batteries".

[0098] Ion conductivity: The test results were obtained in accordance with the standard GB-T 36363-2018 "Polyolefin separators for lithium-ion batteries".

[0099] Interfacial adhesion strength with the electrode: The composite separator was cut into test strips with a width of 25 mm and a length of 60 mm, and the negative electrode was cut into test strips with a width of 25 mm and a length of 40 mm. The first adhesive layer side of the cut composite separator test strip and the electrode were bonded together with 3M tape. After bonding, two strips of white paper (the size of the white paper strips is larger than the size of the separator test strip) were sandwiched between them. The strips were then pressed (hot-pressed) at 60℃ and 1MPa for 1 min. After natural cooling at room temperature, the composite separator test strip and the electrode were partially peeled off to form the clamping part. The composite separator test strip and the negative electrode, which had been hot-pressed and cooled to room temperature, were then placed in the clamping space of a tensile testing machine for a 180° peel test. The test speed was 300 mm / min and the gauge length was 100 mm. The peel strength was recorded in gf / 25 mm to obtain the interfacial adhesion strength between the composite separator and the electrode, which characterizes the adhesion between the composite separator and the electrode.

[0100] The test results are shown in Table 3.

[0101] Table 3

[0102]

[0103] The mechanical strength of the composite membrane is mainly related to the material and structure of the base membrane. Generally speaking, the mechanical strength of the first base membrane with a three-dimensional network structure is significantly higher than that of the second base membrane with a through-hole structure. In the above embodiments and comparative examples, the composite membrane of Example 3 has the best mechanical strength, the composite membrane of Example 2 has relatively high mechanical strength, and the composite membrane of Comparative Example 3 has the lowest mechanical strength. This is mainly because the first base membrane of Comparative Example 3 is a PET film with through holes, which leads to a decrease in its mechanical strength. In addition, for base membranes of the same material, their mechanical strength is positively correlated with their thickness.

[0104] The interfacial adhesion strength between the composite diaphragm and the electrode is related to the first adhesive layer. Compared with Comparative Example 1, the interfacial adhesion strength between the composite diaphragm and the electrode in each embodiment is significantly improved.

[0105] Generally, ionic conductivity depends primarily on the length of the ion migration path within the battery. Compared to separators with large pore structure tortuosity and large thickness, separators with a straight-through pore structure and low thickness provide shorter ion migration paths, thus exhibiting higher ionic conductivity. Comparison of ionic conductivity test results for various composite separators shows that embodiments with thinner overall thickness and straight-through pores all exhibit higher ionic conductivity.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this utility model, and are not intended to limit it. Although the utility model has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this utility model.

Claims

1. A composite diaphragm, characterized in that, The material includes a first adhesive layer, a first base film, a second adhesive layer, and a second base film stacked sequentially. The first base film has a through-hole structure, the second base film has a porous three-dimensional network structure, and the second adhesive layer has an island structure. The first adhesive layer has a through-hole structure, and the through-holes of the first adhesive layer correspond to and are interconnected with the through-holes of the first base film.

2. The composite diaphragm according to claim 1, characterized in that, The thickness of the second adhesive layer is 0.1 μm to 1 μm.

3. The composite diaphragm according to claim 1 or 2, characterized in that, The composite membrane also includes an adhesive polymer, which is disposed on the sidewall of the through-hole of the first base membrane and close to the second base membrane.

4. The composite diaphragm according to claim 3, characterized in that, The stacking height of the adhesive polymer is 0.1 μm to 2 μm.

5. The composite diaphragm according to claim 3, characterized in that, The adhesive polymer is selected from one of polyimide, polyetherimide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, polyvinyl alcohol, epoxy resin, polyurethane or polyvinyl acetate.

6. The composite diaphragm according to any one of claims 1-5, characterized in that, The pore density of the through-holes in the first base film is 2×10⁻⁶. 9 pcs / m 2 ~2×10 10 pcs / m 2 ; And / or, the average pore size of the through-holes in the first base film is 1 μm to 10 μm; And / or, the thickness of the first base film is 5 μm to 10 μm.

7. The composite diaphragm according to any one of claims 1-6, characterized in that, The first base film is selected from one of polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalenedicarboxylate.

8. The composite diaphragm according to any one of claims 1-7, characterized in that, The thickness of the second base film is 3μm~5μm; And / or, the average pore size of the pores in the second base film is 1 nm to 100 nm; And / or, the porosity of the second base film is 30%~60%.

9. The composite diaphragm according to any one of claims 1-8, characterized in that, The second base film includes a polyolefin substrate, or a polyolefin substrate and a coating disposed on at least one surface of the polyolefin substrate, wherein the coating is selected from inorganic ceramic coatings, organic polymer coatings or nanofiber coatings.

10. The composite diaphragm according to claim 9, characterized in that, The polyolefin substrate is selected from at least one of polyethylene film, polypropylene film, and polybutene film, or a composite substrate film formed by laminating any two of them.

11. The composite diaphragm according to any one of claims 1-10, characterized in that, The thickness of the first adhesive layer is 0.1 μm to 2 μm; And / or, the average pore size of the through holes in the first adhesive layer is 1 μm to 10 μm.

12. The composite diaphragm according to any one of claims 1-11, characterized in that, The first adhesive layer and the second adhesive layer are each independently selected from one of polyimide, polyetherimide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, polyvinyl alcohol, epoxy resin, polyurethane or polyvinyl acetate.

13. A battery, characterized in that, Includes the composite diaphragm according to any one of claims 1-12.